2004
DOI: 10.1073/pnas.0408439102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibronectin splicing in sinusoidal endothelial cells from normal or injured liver

Abstract: Fn containing an extra type III domain (EIIIA in the rat, ED1 or EDA in humans) is commonly termed ''fetal'' fibronectin, but it is prominent during the injury response of adult tissues and mediates important early events in the response. This form is particularly apparent in acute liver injury, where it has been shown that sinusoidal endothelial cells produce EIIIA-fibronectin. This fibronectin isoform arises by alternative splicing of the primary transcript. In the present experiments, we have studied the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In these animals the loss of ILK resulted in profound defects in cell spreading, adhesion, actin organization, and proliferation. 49 Therefore, on the basis of our findings as well as those of others, 36,50 we speculate that binding of HSCs to fibronectin via its integrin receptors triggers the activation of FAK, PI3K, ILK, and the AKT/PKB pathway, thus inducing activation of HSCs and enhancing their migration and proliferation. ILK also upregulates the expression of MAP and Erk 1/2 kinases, and these can further influence cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 83%
“…In these animals the loss of ILK resulted in profound defects in cell spreading, adhesion, actin organization, and proliferation. 49 Therefore, on the basis of our findings as well as those of others, 36,50 we speculate that binding of HSCs to fibronectin via its integrin receptors triggers the activation of FAK, PI3K, ILK, and the AKT/PKB pathway, thus inducing activation of HSCs and enhancing their migration and proliferation. ILK also upregulates the expression of MAP and Erk 1/2 kinases, and these can further influence cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 83%
“…However, specific functional roles for EIIIA and EIIIB have been difficult to identify. EIIIA has been implicated in cell differentiation (Chang et al, 2004) and cell adhesion (Liao et al, 2002). However, constitutive exclusion of EIIIA is not life-threatening; EIIIA À / À mice show abnormal skin wound healing (Muro et al, 2003) and smaller atherosclerotic lesions (Tan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of EIIIA+ cFN is minimal in the healthy liver, but TGFβ induces its upregulation within 12 hours of liver injury 12, 13 . A 1994 study showed that primary hepatic stellate cells cultured on EIIIA+ cFN express higher levels of αSMA than do those cultured on pFN 14 , suggesting that EIIIA promotes fibrosis.…”
Section: Introductionmentioning
confidence: 99%